Manajemen Usaha Perikanan Laut Berbasis Kelompok Usaha Bersama (KUB) Nelayan Tangkap Kelas Kub Mina Klatak Di Desa Keboireng Di Kabupaten Tulungagung - Azmi, Ulul; Daroini, Ahsin; Saputra, Beny Mahyudi (Universitas Islam Kadiri, 2024)
Keboireng Village in Tulungagung, East Java, is a coastal area where most of the population depends on the fisheries sector. The high level of poverty among fishermen and gender inequality in the distribution of roles and economic benefits are major challenges. This study aims to analyze the role of KUB Mina Klatak in efforts to alleviate poverty, improve gender equality, and maintain the sustainability of marine ecosystems in Keboireng Village. By understanding the dynamics and contributions of this KUB, it is hoped that it can provide policy recommendations that can be applied in other areas with similar characteristics. The case study method is used to examine in depth the role of KUB Mina Klatak in poverty alleviation, gender empowerment, and marine ecosystem preservation in Keboireng Village. Triangulation of analytical data was carried out by combining interviews, direct observation, and document analysis to ensure the validity and reliability of the research findings. Results Discussion KUB Mina Klatak has succeeded in improving the economic welfare of fishermen through a collective approach in resource management and marketing of catches. With this cooperative, fishermen can reduce operational costs and get better prices in the market. Empowering women through training and active involvement in KUB management has improved gender equality, with women now having a greater role in decision-making and the family economy. The KUB also promotes sustainable fishing activities, which help preserve the marine ecosystem. The Mina Klatak KUB in Keboireng Village has become an effective model for poverty alleviation by empowering fishing communities, especially women, and promoting sustainable fishing practices. The success of this KUB shows that a collective and inclusive approach can be a solution to address socio-economic and environmental challenges, and can be replicated in other coastal areas.